Implementasi Kebijakan Ruang Terbuka Hijau di Kota Pekanbaru - Yenni Syafwardi; Zulkarnaini Zulkarnaini (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the implementation of green open space (GOS) policy in Pekanbaru City and to identify the supporting and inhibiting factors in its execution. Green open spaces play a vital role in maintaining urban ecosystem balance, improving environmental quality, and providing beneficial public spaces for the community. This research uses a qualitative approach with data collected through interviews, observations, and document analysis. The findings indicate that the implementation of GOS policy in Pekanbaru City has not been fully optimized. Several challenges were identified, including limited land availability, lack of inter-agency coordination, and minimal community participation. Nevertheless, the city government has made efforts to increase the quantity and quality of GOS through greening programs and the development of urban parks. This study recommends strengthening regulations, enhancing cross-sectoral synergy, and actively involving the community in the planning and management of GOS to support the achievement of sustainable urban development goals.